2014
DOI: 10.1039/c4tc00822g
|View full text |Cite
|
Sign up to set email alerts
|

Constitutional isomers of a C3-symmetric molecule showing different piezochromic behaviours: on–off switching and colour tuning

Abstract: Two constitutional isomers of a C3-symmetric molecule having cyano-vinylene bridges and a phenyl ring core show different piezochromic behaviours, on–off switching and colour tuning upon grinding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…CS with fluoro substitution and phenothiazine luminescent units show MCF properties with red‐shifted emission, whereas other halogen groups (Cl, Br) did not give rise to this property. Two isomeric C 3 ‐symmetric molecules with a bromo terminal group (Figure D) were found to exhibit MCF, whereas unsubstituted compounds did not show this behavior . Upon grinding, the isomer with inner CN groups, α‐BPAN‐Br (Figure D) exhibited substantial quenching of bluish green emission, which represents a case of fluorescence turn‐off, while the one with CN groups in the outer position, β‐BPAN‐Br , showed a color change from bluish green to deep blue.…”
Section: Solid‐state: Polycrystalline Powders Single Crystals and Tmentioning
confidence: 98%
See 1 more Smart Citation
“…CS with fluoro substitution and phenothiazine luminescent units show MCF properties with red‐shifted emission, whereas other halogen groups (Cl, Br) did not give rise to this property. Two isomeric C 3 ‐symmetric molecules with a bromo terminal group (Figure D) were found to exhibit MCF, whereas unsubstituted compounds did not show this behavior . Upon grinding, the isomer with inner CN groups, α‐BPAN‐Br (Figure D) exhibited substantial quenching of bluish green emission, which represents a case of fluorescence turn‐off, while the one with CN groups in the outer position, β‐BPAN‐Br , showed a color change from bluish green to deep blue.…”
Section: Solid‐state: Polycrystalline Powders Single Crystals and Tmentioning
confidence: 98%
“…[23c] Copyright 2014, The Royal Society of Chemistry. (D) Adapted with permission . Copyright 2014, The Royal Society of Chemistry.…”
Section: Solid‐state: Polycrystalline Powders Single Crystals and Tmentioning
confidence: 99%
“…Copyright 2014, The Royal Society of Chemistry. Part (d) is adapted with permission . Copyright 2014, The Royal Society of Chemistry.…”
Section: Mechanically Induced On–off Switchingmentioning
confidence: 99%
“…After the report on 32 , another research group achieved photoluminescence on–off switching using cyano‐substituted stilbene derivatives. Chang et al have developed C 3 ‐symmetric molecules having p ‐bromophenyl moieties . The authors found that compound 33 having cyano substituents at the α ‐position to the central phenyl moiety exhibits on–off switching in photoluminescence upon mechanical stimuli (Figure d).…”
Section: Mechanically Induced On–off Switchingmentioning
confidence: 99%
“…[23] The capture of carbon in P1 comes mostly from its high porosity, which clearly relates the uptake in the other networks to their cyanovinyl content, making the latter a very interesting building block for carbon capture. Even for P4, which consists only of cyanostilbene units that are not entirely linear but rather more flexible and could relax into a nonporous condensed state, [24] the functional group maintains the polymer with an uptake of 32 mg of CO2 per 1 g of material. It is noted however that selectivities of these networks over N2 were relatively poor.…”
Section: Nitrogen Sorption Properties Of the Mpns P1-p4 And Their Carmentioning
confidence: 99%